Decentering, Acceptance, and Non-Attachment: Challenging the Question “Is It Me?” - Soler, Joaquim; Montero-Marin, Jesus; Domínguez-Clavé, Elisabet; González, Sara; Pascual, Juan Carlos; Cebolla, Ausiàs; Demarzo, Marcelo; Analayo, Bhikkhu; García-Campayo, Javier (Frontiers in Psychiatry, 2021)
Among mindfulness measures the three constructs acceptance, decentering and non-attachment are psychometrically closely related, despite their apparent semantic differences. These three facets present robust psychometric features and can be considered core themes in most “third wave” clinical models. The aim of the present study was to explore the apparently different content domains (acceptance, decentering, and non-attachment) by administering various psychometric scales in a large sample of 608 volunteers. Resilience and depression were also assessed. Exploratory and confirmatory factor analyses performed in two randomly selected subsamples showed a bifactor approximation. The explained common variance suggested a unidimensional nature for the general factor, with good psychometric properties, which we named “Delusion of Me” (DoM). This construct is also strongly correlated with resilience and depression, and appears to be a solid latent general construct closely related to the concept of “ego”. DoM emerges as a robust, potentially transdiagnostic construct, with a powerful influence on well-being and clinical indexes such as resilience and depression. Further studies should analyse the potential utility of this new construct at a therapeutic level.